1995
DOI: 10.1126/science.7725112
|View full text |Cite
|
Sign up to set email alerts
|

Thumbs, Tools, and Early Humans

Abstract: senting cells. Contributions from Gleichmann's laboratory have provided another dimension for this approach by examining lymphoproliferative responses to different xenobiotics in vivo. This work complements our studies because it demonstrated that immune reactivity was not against the administered compound, but a metabolite of higher oxidation state; we showed how such products could be produced within a lymphoid compartment.In order to account for the autoimmune side effects of drugs, Gleichmann and colleague… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 5 publications
2
19
1
Order By: Relevance
“…Gorillas' distal phalanges show some shape similarity to those of humans; they are tapered distally but are "capped by a horse-shoe rim of bone which approaches in relative breadth the arrangement in man" (Marzke, 1964: 151). The radioulnarly wide first metacarpal head of gorillas (Hamrick and Inouye, 1995;Ohman et al, 1995) also suggests that other factors besides selection in favor of the sorts of manipulation involved in tool use can produce convergent results. The expanded first metacarpal head of gorillas is all the more telling as an example because their relatively short thumbs are not the digits primarily stressed in their knuckle-walking mode of locomotion.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Gorillas' distal phalanges show some shape similarity to those of humans; they are tapered distally but are "capped by a horse-shoe rim of bone which approaches in relative breadth the arrangement in man" (Marzke, 1964: 151). The radioulnarly wide first metacarpal head of gorillas (Hamrick and Inouye, 1995;Ohman et al, 1995) also suggests that other factors besides selection in favor of the sorts of manipulation involved in tool use can produce convergent results. The expanded first metacarpal head of gorillas is all the more telling as an example because their relatively short thumbs are not the digits primarily stressed in their knuckle-walking mode of locomotion.…”
Section: Discussionmentioning
confidence: 92%
“…Regression analyses of distal phalanx 1 radioulnar tuft width on base width allow comparison with the results of Susman (1988); regression analyses of metacarpal 1 radioulnar head width on metacarpal 1 maximum length likewise extend research on the value of this metacarpal ratio (Susman, 1994;Hamrick and Inouye, 1995;Ohman et al, 1995). Due to the use of the regressions for comparison and functional interpretation, reduced major axis (RMA) regression is the technique of choice (Aiello, 1992).…”
Section: Analysesmentioning
confidence: 98%
See 1 more Smart Citation
“…The relatively narrow thumbs of these apes may reflect a morphological adaptation to facilitate the powerful hook grip required for arm-swinging (Napier, 1960), which could explain why gorillas, the most terrestrial of the apes, have thumbs that are more robust than those of Pan, Pongo or Hylobates (Hamrick and Inouye, 1995;Ohman et al, 1995). Our findings underscore the need to consider ecological factors and associated behavioral and artifactual evidence when applying a single-trait anatomical test to distinguish primate species that use tools from those that do not (Hamrick and Inouye, 1995;McGrew, 1995;Ohman et al, 1995;Susman, 1994Susman, , 1995. Our findings underscore the need to consider ecological factors and associated behavioral and artifactual evidence when applying a single-trait anatomical test to distinguish primate species that use tools from those that do not (Hamrick and Inouye, 1995;McGrew, 1995;Ohman et al, 1995;Susman, 1994Susman, , 1995.…”
Section: Discussionmentioning
confidence: 99%
“…McGrew (1995) noted that even with relatively weak thumbs great apes use tools in a variety of contexts and that to deny tool behavior to early Australopithecines on the basis of having ape-like thumbs was therefore unfounded. Hamrick and Inouye (1995) and Ohman et al (1995) provided anatomical data for gorillas, orangutans, and gibbons which indicated that thumb robusticity for many gorillas extends into the range of Homo and the robust Australopithecines, thereby challenging the value of Susman's test to distinguish between species that use tools and those that do not. Susman (1995) responded by arguing that even though early Australopithecines may have used tools in an ape-like manner there are neither tools nor evidence of tool-use to support such a claim.…”
Section: Introductionmentioning
confidence: 99%